2015
DOI: 10.4995/ia.2015.4113
|View full text |Cite
|
Sign up to set email alerts
|

El impacto del riego en la calidad del agua de drenaje en una nueva zona regable

Abstract: Villar et al. | El impacto del riego en la calidad del agua de drenaje en una nueva zona regable 241 Ingeniería del Agua | 19. 4 | 2015 El impacto del riego en la calidad del agua de drenaje en una nueva zona regable RESUMENLa calidad del agua de dos sistemas de drenaje agrícola fue monitorizado en dos temporadas de riego para determinar la sostenibilidad de una zona recientemente transformada de secano a regadío y gestionada por la Comunidad de Regantes del Canal de Algerri-Balaguer, en el Noreste de Espa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Salt loads under sprinkler irrigation from VID were similar to other sprinkler irrigated areas at the Middle Ebro River Basin (between 5 and 7 Mg/ha) without gypsum or salt substrates (Causapé, 2009;CITA-CHE, 2017;García-Garizábal and Causapé, 2010;Villar et al, 2015). Nevertheless, salt loads from other basins under sprinkler irrigation, with gypsum or salt substrate, were around 13-14 Mg/ha (CITA-CHE, 2017;Tedeschi et al, 2001).…”
Section: Salt Inputs and Outputssupporting
confidence: 51%
“…Salt loads under sprinkler irrigation from VID were similar to other sprinkler irrigated areas at the Middle Ebro River Basin (between 5 and 7 Mg/ha) without gypsum or salt substrates (Causapé, 2009;CITA-CHE, 2017;García-Garizábal and Causapé, 2010;Villar et al, 2015). Nevertheless, salt loads from other basins under sprinkler irrigation, with gypsum or salt substrate, were around 13-14 Mg/ha (CITA-CHE, 2017;Tedeschi et al, 2001).…”
Section: Salt Inputs and Outputssupporting
confidence: 51%
“…The purpose of such indices is generally to allow comparison between irrigation districts or sub-basins, but it also enables the establishment of a benchmark to know the possibilities of improving irrigation water management. During the studies carried out in others sub-basins of the irrigated area in 2006 and 2008 [34], with less intensive monitoring and monthly data sampling, a DR between a 7% and 18% was estimated. In that study, results showed a drainage discharge during August between 0.11 and 0.396 mm/day, which are lower than the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The drainage network was built following the natural drainage system existing in the zone previously. Prior studies in irrigation and drainage were carried out during 2006 and 2008, when lower amount of land was irrigated [34].…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation was performed by sprinklers with presumably good quality water. Physicochemical parameters of the irrigation water used in the area are collected in (Villar Mir et al, 2015). The composition of Fig.…”
Section: Site Description and Experimental Settingmentioning
confidence: 99%